Pancasila sebagai dasar negara paradigma berbangsa dan bernegara: Menjadikan pancasila sebagai cerminan kehidupan berbangsa dan bernegara yang berkelanjutan - Tasya Dimarcha, Haya Haura (Maliki Interdisciplinary Journal, 2025)
Pancasila, as Indonesia’s state foundation, holds a fundamental role in shaping a just, civilized, and sustainable national life. The values it embodies divinity, humanity, unity, democracy, and social justice serve as the moral compass uniting the Indonesian people amidst cultural, ethnic, and religious diversity. This study aims to examine the role of Pancasila as a paradigm for the life of the nation and to identify the current challenges in implementing its values in the era of globalization and digital transformation. The research applies a qualitative descriptive approach through library research, drawing upon various nationally indexed academic sources. The findings reveal that Pancasila functions not only as a constitutional foundation but also as a living philosophy guiding the nation’s social, political, economic, and cultural behavior. However, the rise of integrity crises, the decline of communal solidarity, and the increasing social polarization indicate a gradual erosion of Pancasila’s moral essence. Therefore, revitalizing Pancasila through character education, moral leadership, fair law enforcement, and digital literacy grounded in national ethics is essential to sustain an ethical, just, and harmonious society.